Edukasi Urgensi Pemeriksaan Golongan Darah dan Aplikasinya pada Santriwati Al-Fityan School Aceh - Safwan; Hadijah, Siti; Darmawati; Erlinawati; Putri, Safridha Kemala; Fitriana; Fajarna, Farah; Syahnita, Hastuti; Situmorang, Paska Ramawati; Mutia, Liza; Lubis, Nita Andriani; Lasmini, Titi; Rosmiati, Karolina; Wardhani, Sri Muri Dasa (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
Blood type is important for human life and is very useful in medical matters such as determining the blood type of parents and children, the success of medical procedures such as blood transfusions and organ transplants. Transfusion of blood from an incompatible group causes an immunological transfusion reaction resulting in hemolytic anemia, kidney failure, shock and death. Most of the students of Al-Fityan School Aceh's tahfiz program do not know their blood type. Apart from that, the students of the Al-Fityan School Aceh tahfiz program have minimal knowledge about blood types. The aim of this community service is to increase students' knowledge about the urgency of checking blood types and its application in everyday life. The target of this community service is the female students of the Al-Fityan School Aceh tahfiz program, consisting of 47 people. The implementation begins with education first and continues with a blood type check. Examination Results: The blood group of the female students of Tahfis Al- Fityan School Aceh is blood group O, namely 70% (31 people), while blood groups A and B are 12.8% (6 people) respectively and the smallest blood group frequency is blood group AB, namely 8.5% (4 people).